EFFECT OF PROFITABILITY, LEVERAGE, AND DIVIDEND POLICY ON STOCK PRICES ON PRIMARY AND NON-PRIMARY CONSUMER GOODS SECTOR COMPANIES: PENGARUH PROFITABILITAS, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER DAN NON-PRIMER - Zico Figli; Achmad Fauzi; Ati Sumiati (Yayasan Education and Social Center, 2022)
This research aims to determinate the effect of Profitability, Leverage, and Dividend Policy on Stock Prices. The data collection method used is Study Documentation method. The affordable collection in this study was consumer cyclicals and non-cyclicals companies listed on Indonesia Stock Exchange (IDX) in 2020 with total 225 companies. Data collection by collecting data on annual financial report in Indonesia Stcok Exchange (IDX) web. This research used purposive sampling with total sampel used were as many 48 companies reduced by companies match with criteria. The data analysis techniques used is multiple linear regression analysis, desciptive statistics analysis, pre-requirement test analysis, classic assumption test, and hypothesis test. Multiple linear regression analysis indicate between variable have relation. Desciptive statistics analysis indicate overview of each variable. Pre-requirement test analysis indicate data is distributed normal. Classic assumption test indicate data acceptable. And hypothesis test result use tu conclude that all hypotheses acceptable or rejectable. Based on the analysis, it is shown that profitability have positive effect on stock price. While Leverage and Dividend Policy has no effect on stock price. Then the coefficient determination in this study was 13,8% which showed the ablity of profitabiliy, leverage, and dividend policy on stock price on influencing stock price while the rest were influenced by other factors that not examined.